Penggunaan Teknologi Informasi Dan Pengaruhnya Terhadap Kinerja Individual Pada Dinas Perhubungan Komunikasi Dan Informatika Surakarta - Estantyono, Vatio, Drs. Suyatmin Waskito Adi, M.Si (2016)
This study aims to examine and analyze the factors that influence the information technology utilization and its impact on individual performance in the Dinas Perhubungan Komunikasi dan Informatika Surakarta. With the technology, stimulate organizations to learn about information technology that can be utilized to the maximum so as to provide a positive impact on performance. This study uses a model developed by Thompson et al. (1991) to examine the influence of social factors, Affect, komplektisitas, suitability duty, long term consequences and conditions that facilitate the information technology. It is also used research model that combines the information technology utilization with the performance developed by Goodhue and Thompson et al. (1995). Samples were 38 employees at the Dinas Perhubungan Komunikasi dan Informatika Surakarta. Data is collected and used to predict the information technology utilization on individual performance. The data is processed by multiple linear regression and simple regression through SPSS. Our results show the complexity factor and job fit effect the information technology utilization. While social factors, long-term consequences, the conditions that facilitate and Affect no effect on the information technology utilization. The test results also show that the information technology utilization effect the individual's performance. The results of this test supports TAM (tecnology accecptance model) which states that the information technology utilization can affect the performance. Keywords: individual performance, the information technology utilization, social factors, job fit, long-term consequences, conditions that facilitate, complexity, affect.